PENGARUH KUALITAS PELAYANAN, KUALITAS PRODUK DAN PROMOSI TERHADAP KEPUASAN PELANGGAN DI RESTORAN UCCELLO - Dyah Kumala Sari; Salman Paludi (Panorama Nusantara, 2020)
This study aimed to determine and analyze the influence of service quality, product quality, and promotion on customers satisfaction in Uccello Restaurant. The population in this research are customers of Uccello Restaurant from April to August 2019. The sampling technique used non probability sampling, with purposive sampling method to determine 100 respondent. The data collection by accidental technique using the questionnaire that has been tested for validation and reliability. The analytical method used the Clasic test, before Multiple Linear Regresion by SPSS 20. The 100 respondents as a tool, followed by F, t, Correlation and Determination Test. The results of this study prove that partially, the variable service quality has significantly effect on customers satisfaction, the variable product quality has significanly effect on customers satisfaction, and the variable promotions has significanly effect on customers satisfaction. Therefore, variables service quality, product quality and promotion simultaneously affect to customers satisfaction.